SONGS OF MAHZANI OF WOLOAN AND RUKUKAN: FROM RITUAL TO PERFORMANCE - Manus, Jeane Angela; Limbong, Priscila Fitriasih Fitriasih; Setyani, Turita Indah; Yoesoef, Muhammad (International Review of Humanities Studies, 2026)
As one of oral traditions acknowledged in Woloan and Rurukan, Tomohon Minahasa, the songs of mahzani have long been sung in these two areas. As we understand that oral tradition would disappear from its community when it has lost its real function, this particular oral tradition has developed into staged performances. Songs of mahzani that had been practiced for generations as part of the mapalus traditions in the last decades has significantly decreased in line with the change of lifestyle of the people who practice it. Using qualitative method with an ethnographic approach, this article is to delve into the shift of function of mahzani songs. Data are drawn from two village: Woloan and Rurukan in Tomohon Minahasa.